The Potential Use of EDTA as an Alternative to Defibrination in Preparing Blood Agar Plates with Human AB Blood Type on Staphylococcus aureus Culture - Turista, Dora Dayu Rahma; Puspitasari, Eka; Razvi, Fanny Kurnanda (Universitas Nahdlatul Ulama Surabaya, 2021)
Blood Agar Plates (BAP) are composed of blood as one of the compositions. Sheep’s blood is usually used, but since it is difficult to be obtained, human AB blood type was used as an alternative. In preparing BAP, blood is defibrinated to lyse the blood clotting factors. Blood clots can also be prevented by adding anticoagulants, such as ethylenediaminetetraacetic acid (EDTA). This study aims to investigate the potential use of EDTA as a substitute for defibrination in preparing BAP with human AB blood type. This study employed a completely randomized design with true experimental method using Staphylococcus aureus as the sample. The parameters were the number of colonies, types of hemolysis, and hemolysis zone. The results showed that the S. aureus grown on BAP with EDTA-human AB blood type was 64 colonies (mean), produced β-hemolytic pattern, and 6 mm hemolytic zone. In contrast, the S. aureus grown on BAP with defibrinated human AB blood type showed 82 colonies (mean), β-hemolytic pattern, and 5 mm hemolytic zone. There were significant differences in the number of colonies (0.000 < α) and hemolytic zones (0.02 < α). However, there was no difference in the hemolysis type (both treatments produced β-hemolysis). EDTA was possible to be used as a substitute for defibrination in preparing BAP to assess the hemolysis type of S. aureus, but it might not be able to be used as a benchmark for counting the number of colonies and determining the hemolysis zone of S. aureus.